Design of Traction Control Unit Based on CPCI Bus - YIN Zhenhuan (机车电传动)
Traction control unit (TCU) is the key and core component of traction system on China electric multiple unit (CEMU). Based on the analysis of TCU system functions of CEMU and top-level design, the hardware and software platform of TCU based on CPCI high-speed data bus was designed and realized. Ground test in AC drive laboratory of independently developed TCU was finished, and the CEMU loaded with independently developed TCU had begun passenger operations on main line, loading appraisals well, which verified the reliability and availability of TCU hardware and software platform.